Cognitive Bias and Green Investment Decision-Making among Finansial Management Students in Medan City: The Moderating Role of Financial Literacy - Muhammad Riyadul Afkar; Syahyunan; Amlys Syahputra Silalahi (Journal of Business Management, 2026)
Green investment has grown rapidly as a sustainable financial instrument, yet the decision-making quality of young investors is frequently distorted by psychological factors and irrational behavior. This study analyzes the effects of cognitive biases overconfidence, herding, representative, and status quo bias on green investment decisions among financial management students in Medan, Indonesia, while evaluating the moderating role of financial literacy. A quantitative survey was administered to 187 students selected through proportionate stratified random sampling from seven universities. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. The findings demonstrate that overconfidence, herding, representative, and status quo biases exert significant negative effects on green investment decision quality, whereas financial literacy has a significant positive effect. Financial literacy further moderates all four relationships by weakening the negative influence of each bias, thereby guiding students toward more rational decisions. The model explains 79.8% of the variance in green investment decisions (R² = 0.798), with strong predictive relevance (Q² = 0.630) and a very high overall model fit (GoF = 0.865). These results confirm that sustainable investment decisions are shaped not only by financial calculations but also by psychological control. Strengthening financial education programs that integrate sustainable finance principles is therefore critical to minimizing cognitive distortion and optimizing green portfolio quality among prospective retail investors.